PENGARUH COGNITIVE SKILLS TERHADAP HASIL BELAJAR MATEMATIKA SECARA DARING - Wahyuddin Wahyuddin; Muhammad Awal Nur; Sri Satriani (Jupitek)
The covid 19 pandemic that occurred resulted in the learning process being carried out online, but online learning was found to have many obstacles so that in order to make online learning effective, students' cognitive abilities must be optimized. This quantitative study aims to analyze the cognitive skills of students that can influence online mathematics learning outcomes and to describe the cognitive skills variables that have the dominant influence. This research is a quantitative survey research conducted in January-March 2021 involving 155 high school students in Makassar City, consisting of 95 women and 60 men. The research variables consisted of exogenous variables, namely cognitive skills (metacognition, reading comprehension ability, cognitive needs, and intelligence), while the endogenous variables were the results of learning mathematics. The instruments used to measure exogenous variables are questionnaires and intelligence tests that meet the validity and reliability tests. The endogenous variable is learning outcomes obtained from the documentation value of students' mathematics learning outcomes (report scores). The data was processed by descriptive analysis and inferential analysis using structural equation modeling (SEM). The results of the study indicate that metacognition and intelligence have a positive and significant effect on online mathematics learning outcomes, it means that the higher the metacognition and intelligence possessed by students, the student's learning outcomes will increase. Meanwhile, reading comprehension skills and cognitive needs were found to have no significant effect on online mathematics learning outcomes, this means that reading comprehension skills and cognitive needs have not provided sufficient evidence that they can affect online mathematics learning outcomes. The cognitive skills variable that gives the dominant influence on online mathematics learning outcomes is intelligence with a contribution of 19.53%. This shows that intelligence has a great influence on the online learning process of mathematics